2016
DOI: 10.1371/journal.pone.0153587
|View full text |Cite
|
Sign up to set email alerts
|

HO-1 Protects against Hypoxia/Reoxygenation-Induced Mitochondrial Dysfunction in H9c2 Cardiomyocytes

Abstract: BackgroundMitochondrial dysfunction would ultimately lead to myocardial cell apoptosis and death during ischemia-reperfusion injuries. Autophagy could ameliorate mitochondrial dysfunction by autophagosome forming, which is a catabolic process to preserve the mitochondrial’s structural and functional integrity. HO-1 induction and expression are important protective mechanisms. This study in order to investigate the role of HO-1 during mitochondrial damage and its mechanism.Methods and ResultsThe H9c2 cardiomyoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
1
24
0
1
Order By: Relevance
“…Previous studies have demonstrated that hypoxia caused injury via regulating autophagy [9, 27]. Consistent with these reports, our findings showed that hypoxia induced autophagy and endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have demonstrated that hypoxia caused injury via regulating autophagy [9, 27]. Consistent with these reports, our findings showed that hypoxia induced autophagy and endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, ROS was crucial in hypoxia-induced autophagy [26, 27]. Therefore, we further explored if ROS plays a role in CLOCK-induced cell autophagy and dysfunction in HUVECs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Chen et al . ). We hypothesized that both heat pretreatment and exposure to heat therapy serum would upregulate HO‐1 and that it would remain elevated following H/R.…”
Section: Introductionmentioning
confidence: 97%
“…Secondly, we investigated potential mechanisms behind heat therapy-mediated protection against H/R. Haemeoxygenase-1 (HO-1), which is also an HSP (Hsp32), is capable of suppressing NF-κB activation (Chi et al 2014) and has been shown to protect against H/R-induced inflammation (Park et al 2013;Chen et al 2016). We hypothesized that both heat pretreatment and exposure to heat therapy serum would upregulate HO-1 and that it would remain elevated following H/R.…”
Section: Introductionmentioning
confidence: 99%